2005
DOI: 10.1074/jbc.m507977200
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α Triggers Mucus Production in Airway Epithelium through an IκB Kinase β-dependent Mechanism

Abstract: Excessive mucus production by airway epithelium is a major characteristic of a number of respiratory diseases, including asthma, chronic bronchitis, and cystic fibrosis. However, the signal transduction pathways leading to mucus production are poorly understood. Here we examined the potential role of IB kinase ␤ The airway epithelium is the first layer of cellular interaction with airborne antigens and plays a key role in initiating allergic responses. Research over the last decade has established a critical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 40 publications
4
60
0
1
Order By: Relevance
“…Thus, it may regulate cellular differentiation at different sites in different ways. It is noteworthy that when NCI-H292 cells were treated with EGF, only 25% or fewer of the cells became MUC5AC positive in both this study and others (11,59,60). This might reflect heterogeneity in EGF responsiveness and mitotic state of the cells, enabling only a fraction of the cells to respond to Notch signaling, leading to MUC5AC expression.…”
Section: Figurementioning
confidence: 91%
“…Thus, it may regulate cellular differentiation at different sites in different ways. It is noteworthy that when NCI-H292 cells were treated with EGF, only 25% or fewer of the cells became MUC5AC positive in both this study and others (11,59,60). This might reflect heterogeneity in EGF responsiveness and mitotic state of the cells, enabling only a fraction of the cells to respond to Notch signaling, leading to MUC5AC expression.…”
Section: Figurementioning
confidence: 91%
“…Nevertheless, airway diseases with mucous cell hyperplasia, particularly COPD, have elevated levels of these cytokines in the blood as well as in the lungs (39,40). In addition, both IL-1β and TNF-α induce mucous cell hyperplasia in vivo in mouse models (41,42). Both cytokines can also activate NF-κB signaling in airway epithelial cells (43,44), which, as shown above, can lead to the activation of MUC2 expression.…”
Section: Muc2 Expression Regulated By Inflammatory Cytokinesmentioning
confidence: 93%
“…However, another group has shown that TNF-α can also induce MUC5AC expression in NCI-H292 cells through NF-κB. Adenoviral delivery of an IKKB mutant could block MUC5AC's stimulation by TNF-α, both in vitro in human cells as well as in vivo in mice (41).…”
Section: Regulation Of Muc5ac Expression By Nuclear Factor-κbmentioning
confidence: 99%
“…32) Thus, taken together, it is conceivable that the intracellular signaling coordination by NF-κB activation may be essential for PQ-induced MUC5AC gene expression. Nie et al, demonstrated that MAP kinases signaling pathway is directly implicated in regulation of MUC expression.…”
Section: )mentioning
confidence: 99%